Dye adsorption mechanisms in TiO2 films, and their effects on the photodynamic and photovoltaic properties in dye-sensitized solar cells. Issue 34 (14th September 2015) - Hwang, Kyung-Jun; Shim, Wang-Geun; Kim, Youngjin; Kim, Gunwoo; Choi, Chulmin; Kang, Sang Ook; Cho, Dae Won
<x xml:space="preserve">Abstract</x> The dye adsorption kinetics (and dye adsorption amounts) in DSSC have influenced the photoelectric properties and the photodynamic processes.